STUDY OF TRIP GENERATION IN THE AREA OF PALANGKA RAYA UNIVERSITY - Renna Jesisca Sihombing; Tarita Aprilani Sitinjak Trissan; Whendy Trissan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2026)
This study aims to analyze the pattern of trip generation in the Universitas Palangka Raya area in order to identify the faculty with the highest level of activity and to determine the most optimal time characteristics of facility usage. The research method employed is descriptive quantitative, using a survey technique through the distribution of questionnaires to five observed faculties, namely the Department of Fisheries, Faculty of Law, Faculty of Medicine, Faculty of Social and Political Sciences (FISIP), and Faculty of Mathematics and Natural Sciences (FMIPA). The results indicate that faculties with larger population sizes tend to generate higher levels of trip generation. The Faculty of Social and Political Sciences (FISIP) is identified as the faculty with the highest trip generation, which is consistent with its larger number of students, lecturers, and administrative staff compared to other faculties. The findings also show that the Faculty of Social and Political Sciences exhibits the highest level of activity movement, predominantly dominated by the age group under 21 years. It can be concluded that the most optimal activity period within the Universitas Palangka Raya area occurs during peak academic hours